Mechanical properties of hemp fiber‐reinforced thermoset and thermoplastic polymer composites: A comprehensive review - Shahidul Islam; Md. Byzed Hasan; Marija Kodrić; K. Z. M. Abdul Motaleb; Fahmida‐E‐ Karim; Md. Redwanul Islam (SPE Polymers)
Abstract Hemp fibers have mechanical characteristics similar to those of synthetic fibers, which makes them an attractive material for producing environmentally friendly composites. Hemp fibers have excellent mechanical properties and a unique hydrophilicity, requiring for extra attention in composite formulations. Hemp fibers are a very versatile vegetable fiber that is frequently utilized in structural composites. In addition, hemp has shown potential in a variety of other fields, including as sports goods, building, and lighter materials. The present article aims to give a comprehensive summary of the status of sophisticated studies in hemp fiber reinforced composites at present time. The most important research on thermoset and thermoplastic materials reinforced with hemp fiber is compiled and discussed in this publication. This document also provides an overview of the primary attributes of hemp fibers, talks about how to develop these attributes chemically, explains how to create and describe hemp fiber composites, and identifies areas that need more research. In summary, this study ends with several important recommendations and future approaches that draw attention to the issues that require further investigation and potential industrialization of composites. Highlights Advances in hemp fiber extraction and chemical treatments. Performance traits of hemp‐reinforced thermoset and thermoplastic composites. Tribological, and moisture absorption properties of hemp fiber composites. SEM analysis revealing composite structural characteristics. Future applications and sustainability of hemp fiber in polymers.